2011
DOI: 10.1590/s0004-282x2011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and cerebrovascular disease in children with sickle cell anemia from Rio de Janeiro, Brazil

Abstract: The aim of the present work was to examine possible genetic risk factors related to the occurrence of cerebrovascular disease (CVD) in Brazilian population, the frequency of β S -globin gene haplotypes and co-inheritance with α-thalassemia (-α 3.7kb ) and single nucleotide polymorphism of methylenetetrahydrofolate reductase (MTHFR-C677T), Factor V Leiden (FV-G1691A) and prothrombin (PT-G20210A) genes in children from Rio de Janeiro. Ninety four children with sickle cell anemia (SCA) were included, 24 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…4,12 Furthermore, the effects of α-thalassemia on cerebral vasculopathy and stroke risk in SCA have been mixed with some studies showing a protective benefit 1318 while others have not. 10,1921 In the University of Ibadan cohort of SCA patients, α-thalassemia was commonly observed but was not associated with a statistically significant reduction in the frequency of SCA-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…4,12 Furthermore, the effects of α-thalassemia on cerebral vasculopathy and stroke risk in SCA have been mixed with some studies showing a protective benefit 1318 while others have not. 10,1921 In the University of Ibadan cohort of SCA patients, α-thalassemia was commonly observed but was not associated with a statistically significant reduction in the frequency of SCA-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian studies also found a correlation between SCA clinical manifestations, Hb Fand the beta S-globin haplotype ( 8 , 9 , 13 , 19 , 25 , 29 , 30 ) , including more vaso-occlusive crises ( 9 , 29 ) , more infections ( 9 ) and slower growth ( 29 ) in the CAR haplotype, high levels of Hb F ( 13 , 19 , 25 ) and nitrites in the BEN haplotype ( 19 ) , and increased risk of cerebro vascular disease (CVD) in children with the Bantu/atypical haplotype compared to other beta S-globin haplotypes ( 30 ) . Patients with the CAR/BEN haplotype had less painful crises compared to the other haplotypes ( 22 ) .…”
mentioning
confidence: 82%
“…HBA (α‐globin gene) deletion has been associated with normal TCD measurement and with the absence of vasculopathy on MRA images in patients with SCA, suggesting that α‐thalassaemia may play a protective role against cerebral vasculopathy (Hsu et al , ; Bernaudin et al , ; Belisario et al , ). However, in a small case control study, HBA deletion was found not to be significantly associated with reduced risk for specific neurological events (transient ischaemic attacks, ischaemic strokes or haemorrhagic strokes) (Filho et al , ). Taken together, studies evaluating the association between either G6PD or HBA status on cerebral vasculopathy have had mixed results, possibly due in part to the small sample size and in some cases the inherent biases associated with single institution studies.…”
mentioning
confidence: 99%